2011
DOI: 10.1111/j.1365-2753.2011.01775.x
|View full text |Cite
|
Sign up to set email alerts
|

Length of stay as risk factor for inappropriate hospital days: interaction with patient age and co‐morbidity

Abstract: Doctor attitudes and hospital organization are still among the most common reasons for inappropriate in-hospital days of care. Monitoring whether the length of stay is appropriate combined with protocol interventions for scheduling of diagnosis, treatment and discharge are likely to improve efficiency in this area of medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
2
22
0
2
Order By: Relevance
“…Para lidar com a variação das práticas de alta adotadas pelos hospitais, Jarman et al 21 utilizaram o tempo de permanência como variável de ajuste da mortalidade hospitalar, a exemplo de alguns estudos pioneiros 35 . Outros estudos não costumam incluir esta variável, mas sim considerá-la uma medida relacionada ao processo de cuidado e à eficiência técnica 9,36 . A discussão a respeito do significado de determinado padrão do tempo de permanência é complexa, uma vez que seu efeito sobre a mortalidade é ambíguo e os seus determinantes são diversos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Para lidar com a variação das práticas de alta adotadas pelos hospitais, Jarman et al 21 utilizaram o tempo de permanência como variável de ajuste da mortalidade hospitalar, a exemplo de alguns estudos pioneiros 35 . Outros estudos não costumam incluir esta variável, mas sim considerá-la uma medida relacionada ao processo de cuidado e à eficiência técnica 9,36 . A discussão a respeito do significado de determinado padrão do tempo de permanência é complexa, uma vez que seu efeito sobre a mortalidade é ambíguo e os seus determinantes são diversos.…”
Section: Discussionunclassified
“…Além dos motivos clínicos, há práticas gerenciais voltadas para a maior eficiência, que podem estimular a redução no tempo de permanência, e gerar inclusive altas precoces. A disponibilidade de leitos de longa permanência ou unidades de reabilitação também pode afetar o tempo de permanência e não representar necessariamente inadequações no processo de cuidado 19,35,36 . Por outro lado, as mortes ocorridas no primeiro dia de internação podem decorrer da gravidade do caso, barreiras de acesso ou inadequação do cuidado de emergência.…”
Section: Discussionunclassified
“…Due to the generality of the hospital, the presence of various specialties, and the inter-ward relationships, problems with medical counseling and delays are common. In another study by Barisonzo et al conser-vative performance (39%), results of diagnostic tests (21%), and counseling services (18%) were the contributory factors in inappropriateness of admissions or hospital days (2). The results of the study showed that the likelihood of inappropriateness of hospitalization days increased with the prolonged patients' length of hospital stay.…”
Section: Discussionmentioning
confidence: 85%
“…In a study in which AEP was the criterion for the rate of appropriateness or inappropriateness of stays, Soria-Aledo et al found that this rate was 24.6% (8). Conversely, in studies in which the above-mentioned protocol was not the basis of estimation, this rate was reported as 35.3% (2,20,30). This may be due to the issue that such a protocol includes stricter criteria for the evaluation of appropriateness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation